Implementasi Sistem Notifikasi Keadaan Darurat Berbasis Aplikasi Mobile Web dan Arduino Mega Menggunakan Logika Fuzzy - Prayoga Febriandika; Wijaya Kurniawan; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Emergency situation for every human individual Usually a normal condition that has a tendency or potential that is good for humans, property and the environment. At a time when humans experience an emergency, it is very necessary rapid handling to cover the incident. There is no system as a notification between the victim with others, when the victim experiences an emergency. With this tool, the closest family will know the condition of the user in the event of an emergency. Users only have to press the button as a trigger and then pass the sound sensor or send an emergency signal for the system to send notification to the mobile web app, which then the mobile web app as monitioring user by the closest family, and the family will know the last position of the victim through the GPS module when the user . In this research, Fuzzy sugeno method is used to determine a system under the condition that is user condition (normal or emergency). The system prototype is built using several modules and sensors, ie GPS module, ESP8266 Module, Push Button, Sound Sensor, Gyroscope Accelerometer MPU6050 Sensor, and Arduino Mega as microcontroller. Based on the test results of the system can be seen that the calculation of logic Fuzzy manually the same with the output of Fuzzy logic on the system. the level of accuracy on this system of 100% on the accuracy of the data sensor, Fuzzy logic and systems can send a notification upon user experiencing emergencies.